Ultrafast excited-state dynamics of 2, 5-dimethylpyrrole. Issue 22 (17th April 2018) - Yang, Dongyuan; Min, Yanjun; Chen, Zhichao; He, Zhigang; Yuan, Kaijun; Dai, Dongxu; Yang, Xueming; Wu, Guorong
Abstract : The ultrafast excited-state dynamics of 2, 5-dimethylpyrrole is studied in detail following deep UV excitation. Abstract : The ultrafast excited-state dynamics of 2, 5-dimethylpyrrole following excitation at wavelengths in the range of 265.7–216.7 nm is studied using the time-resolved photoelectron imaging method. It is found that excitation at longer wavelengths (265.7–250.2 nm) results in the population of the S1 ( 1 πσ*) state, which decays out of the photoionization window in about 90 fs. At shorter pump wavelengths (242.1–216.7 nm), the assignments are less clear-cut. We tentatively assign the initially photoexcited state(s) to the 1 π3p Rydberg state(s) which has lifetimes of 159 ± 20, 125 ± 15, 102 ± 10 and 88 ± 10 fs for the pump wavelengths of 242.1, 238.1, 232.6 and 216.7 nm, respectively. Internal conversion to the S1 ( 1 πσ*) state represents at most a minor decay channel. The methyl substitution effects on the decay dynamics of the excited states of pyrrole are also discussed. Methyl substitution on the pyrrole ring seems to enhance the direct internal conversion from the 1 π3p Rydberg state to the ground state, while methyl substitution on the N atom has less influence and the internal conversion to the S1 (πσ*) state represents a main channel.